Recovery of DNA from the Acinetobacter calcoaceticus chromosome by gap repair. - Gregg-Jolly, L A (1990)
A strain of Acinetobacter calcoaceticus that demonstrates unusually high competence for natural transformation by linear DNA has proven valuable for analysis of genes and gene clusters associated with aromatic catabolism. The transformation system allowed gap repair to be used to recover mutant chromosomal DNA within recombinant plasmids. The sizes of the recovered fragments, 5 and 7 kilobase pairs in length, indicate that gap repair will be a useful procedure for isolation of wild-type and modified gene clusters from the A. calcoaceticus chromosome.